Effects of fine particle size on the characteristics of coal bottom ash as an environmentally friendly material in concrete production - Al Biajawi, Mohammad I.; Rahimah, Embong; Abdullah, M.M. Al Bakri (Polish Academy of Sciences, 2024)
In the current era, concern about the responsible disposal of industrial waste and its reuse has increased in all societies from the industry. Therefore, the researchers’ institution is focusing its efforts on developing more environmentally friendly products from recycled waste, particularly in the area of sustainable construction. For instance, one of recycled waste is Coal Bottom ash (CBa), a by-product of coal combustion that is produced in large quantities from thermal power plants. The aims of this study to investigate the physical, chemical and element characteristics of CBa obtained from thermal power plant in Malaysia. also, CBa compared with cement characteristics to be used as cement replacement in the concrete mixture. Therefore, numerous tests have been performed to investigate CBa’s physical and chemical characteristics. For physical properties such as specific gravity, particle size analysis, fineness modulus, bulk density and loss on ignition. For chemical properties such as X-ray fluorescence (XRF), X-ray diffraction (XRd), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (Tga) in an effort to obtain sustainable materials from thermal power plant waste. Based on the findings in this study, it can be concluded that CBa can be utilized as cement substitute in the production of concrete mixtures.